High-performance transparent solvent-free silicone resins with stable storage and low viscosity based on new hyperbranched polysiloxanes. (August 2013) - Zhu, M.; Gu, A.; Liang, G.; Yuan, L.
Five new hyperbranched polysiloxanes, for example, methylhydrogen siloxanes (MHSis), with varying concentrations of silicon–methyl (Si-Me) groups were synthesized and characterized, and then a series of MHSi/poly(methylphenylvinylsilicone) (PSi) resins were prepared to investigate the influence of the structures and concentrations of MHSi on the integrated properties of both uncured and cured MHSi/PSi resins. The results show that the compatibility between MHSi and PSi is closely related to the concentration of Si-Me groups in the MHSi as well as the molar ratio of MHSi and PSi. If MHSi has a suitable concentration of Si-Me groups, and the molar ratios of MHSi to PSi are appropriate, transparent MHSi/PSi resins with stable compatibility can be obtained. In addition, these compatible resins show good thermal stability with dynamic mechanical and dielectric properties. They exhibit a great potential for use as high-performance solvent-free silicone resins in either vacuum pressure impregnating process or liquid-molding techniques.